A Review of the Design and Architecture of Starch-Based Dietary Foods. (May 2021) - Bai, Yuxiang; Li, Xiaoxiao; Ji, Hangyan; Wang, Yu; Zheng, Danni; Wang, Yanli; Jin, Zhengyu
Abstract: Carbohydrates, which are mostly present in sugar, starch, and fiber, are one of the main ingredients of food and the primary source of energy in the human diet. Among these three main sources, starch stands out as one of the most abundant reserves of carbohydrates. Investigating starch would not only enhance our understanding of the functionality of starch in the human body but also aid in the design of novel starch-based dietary foods. The present review first provides a state-of-the-art understanding of the various classifications of dietary starches, including rapidly digesting starch (RDS), slowly digesting starch (SDS), and resistant starch (RS). Moreover, both the in vivo and in vitro determination methods of the digestibility of starch-based dietary foods are discussed. Based on the current understanding, present research strategies to design novel starch-based dietary foods through either the direct addition of modified starch or the alteration of processing conditions are highlighted. Furthermore, certain perspectives related to the future research directions of starch-based foods are also included.